Corporate Social Responsibility, its Relationship with Knowledge Management and Intellectual Capital - Avellán-Herrera , Nilda Alexandra (2019)
In the business world, the creation of value through an adequate knowledge management (KM) has become increasingly necessary for the survival of companies in a market that every day demands to be at the forefront of the globalization of information and its vertiginous change. Likewise, we talk about intangible assets such as intellectual capital (CI), which through its components allows creating added value for a company against its competitors. On the other hand, corporate social responsibility (CSR) allows to complement the other variables very well as a source of business competitive advantage and, at the same time, contributes to sustainable development. In this paper, the concepts mentioned above are addressed from a descriptive research level through a bibliographic review of previous investigations mainly of current scientific articles on the subject, aiming to analyze the existing relationship between CSR, CG and the CI in organizations, concluding that a knowledge management model based on moral and ethical values, as well as on social responsibility precepts will enable companies to achieve additional value to differentiate themselves from the competition.